An updated scoping review of migrant health research in Ireland - Anne Cronin; Ailish Hannigan; Nuha Ibrahim; Yuki Seidler; Blessing Olamide Owoeye; Wigdan Gasmalla; Tonya Moyles; Anne MacFarlane (BMC, 2024)
Abstract Background One in five people living in Ireland is a migrant. Understanding the distinctive health needs of this diverse population is essential to provide evidence-based, culturally sensitive primary care services. The aim of this review is to systematically examine changes in migrant health research in Ireland and to inform research, policy and practice in the field. Methods To update a 2017 scoping review of migrant health research in Ireland, we used Arksey and O'Malley's framework, updates by Colquhoun and Peters and the PRISMA-ScR from the Joanna Briggs Institute to search 10 databases covering May 2017 - March 2023. Findings were analysed using the World Health Organisation Strategy and Action Plan for Refugee and Migrant Health 2016-2023, which identifies 9 priority strategic areas (SA). Findings were compared with the 2017 review. Results 62 papers were identified. There has been an increase in studies over time from an average of five per year in the previous review to an average of 10 per year in this review. There is growing interest in research about SA1: Collaborative action on migrant health issues and SA2: Advocacy for the right to health of refugees and migrants - evidenced by an increase of 13% in this review. Similarly to 2017, the majority of papers align with three of the nine WHO Strategic Areas; SA3: Addressing the social determinants of health (24%), SA4: Achieving public health preparedness (29%) and SA5: Strengthening health systems (26%). The volume of research on SA6: Communicable diseases (11%) and SA7: Noncommunicable diseases (19%) remains stable however research on SA8: Health screening and assessment (5%) and SA9: Improving health information and communication (2%) remains low. Conclusions The increase in the volume of research on migrant health in Ireland is notable. The analysis over time illuminates changes in the focus of research studies. Gaps in research about screening, assessment and health information warrant particular attention. It is also necessary to continue paying attention to areas of recent growth and stagnation for a balanced and comprehensive evidence base. Mobilising resources to continue this increase is needed for evidence-based policy and practice.